The role of DNA polymerase activity in human non-homologous end joining - Pospiech, Helmut (Oxford University Press, 2001)
In mammalian cells, DNA double-strand breaks are repaired mainly by non-homologous end joining, which modifies and ligates two DNA ends without requiring extensive base pairing interactions for alignment. We investigated the role of DNA polymerases in DNA-PK-dependent end joining of restriction-digested plasmids in vitro and in vivo. Rejoining of DNA blunt ends as well as those with partially complementary 5′ or 3′ overhangs was stimulated by 20–53% in HeLa cell-free extracts when dNTPs were included, indicating that part of the end joining is dependent on DNA synthesis. This DNA synthesis-dependent end joining was sensitive to aphidicolin, an inhibitor of α-like DNA polymerases. Furthermore, antibodies that neutralize the activity of DNA polymerase α were found to strongly inhibit end joining in vitro, whereas neutralizing antibodies directed against DNA polymerases β and ɛ did not. DNA sequence analysis of end joining products revealed two prominent modes of repair, one of which appeared to be dependent on DNA synthesis. Identical products of end joining were recovered from HeLa cells after transfection with one of the model substrates, suggesting that the same end joining mechanisms also operate in vivo. Fractionation of cell extracts to separate PCNA as well as depletion of cell extracts for PCNA resulted in a moderate but significant reduction in end joining activity, suggesting a potential role in a minor repair pathway.